EIExplorationInvestor: CKX, Inc. Announces Sale of Company for $13.75 Per Share (M2 Presswire, 2007)
The sale transaction and distribution of shares in FX Luxury Realty are intended to allow CKX stockholders to receive a cash return on their CKX investment while continuing to share directly in the exploitation of CKX's [Elvis Presley] and [Muhammad Ali] assets through FX Luxury Realty's real estate projects, which are expected to include Elvis Presley- and Muhammad Ali-themed attractions as well as FX Luxury Realty's other real estate ventures. The sale of CKX will be accomplished through a merger with 19X, Inc., a private company owned and controlled by Mr. Sillerman, Chairman and Chief Executive Officer of CKX, and Simon R. Fuller, a director of CKX and the Chief Executive Officer of 19 Entertainment Limited, a wholly-owned subsidiary of CKX. 19X has informed CKX that it expects to finance the acquisition of CKX through a combination of equity and debt financing, with Mr. Sillerman and Mr. Fuller, as well as other members of senior management, providing a substantial portion of the equity commitment. This release contains "forward-looking statements" within the meaning of Section 27A of the Securities Act of 1933, as amended, and Section 21E the Securities Exchange Act of 1934, as amended and such forward-looking statements are made pursuant to the safe harbor provisions of the Private Securities Litigation Reform Act of 1995. "Forward-looking statements" describe future expectations, plans, results, or strategies and are generally preceded by words such as "may", "future", "plan" or "planned", "will" or "should", "expected," "anticipates", "draft", "eventually" or "projected". You are cautioned that such statements are subject to a multitude of risks and uncertainties that could cause future circumstances, events, or results to differ materially from those projected in the forward-looking statements, including the risks that actual results may differ materially from those projected in the forward-looking statements as a result of various factors, and other risks identified in a companies' annual report on Form 10-K or 10-KSB and other filings made by such company with the Securities and Exchange Commission.